Cell-automaton energy model of the earthquake focus - Kulchytskyi, V. E. (Geofizicheskiy Zhurnal, 2011)
The energy one-dimensional cellular automaton model of a seismic source is offered which represents modification of model of seismicity. The outcomes of numerical calculations are adduced and the comparison of obtained relations to physical model experiments and full-scale observations is given.